The Usual Suspect: Turkey’s Former PM Hüseyin Rauf Orbay’s Journey to India in 1933 - Fehim Kuruloğlu (Yakın Dönem Türkiye Araştırmaları)
This study examines the former Prime Minister of the Republic of Turkey Hüseyin Rauf Orbay’s journey to India in 1933 during his period of exile. This study seeks to explore how and why Orbay chose to travel to India, with a specific emphasis on whether the Turkish Ministry of Foreign Affairs’ fears that Orbay sought to reestablish the Caliphate in some form within India were merited. This study primarily relies upon the relevant correspondence documents from the State Archives in Turkey and concludes that the worries of the Turkish Ministry of Foreign Affairs were much ado about nothing insofar as this study found no evidence that Orbay had made any statements either against Turkey’s leader at the time, Mustafa Kemal Pasha, or in favor of resurrecting the Caliphate in any form.